Stress and suicidal ideation in Korean baby boomers: the mediating effect of mindfulness and meaning in life - Jeong, Yusoo (Frontiers in Psychology, 2023)
Stress has been shown to enhance elderly suicidal ideation. However, the effect of mindfulness and meaning in life on the relationship between stress and suicidal ideation in Korean baby boomers are still unknown. This study investigated (a) a significant correlation between the stress, suicidal ideation, mindfulness, and meaning in life, (b) the mediating effect of mindfulness in the association between stress and suicidal ideation, (c) the serial mediating effect of mindfulness and then meaning in life on the relationship between stress and suicidal ideation. Data were collected from 200 baby boomers (born between 1955-1963) concerning their stress, mindfulness, meaning in life, and suicidal ideation. These findings suggest that if interventions directed at baby boomers can successfully improve their mindfulness and by extension raise their meaning in life, suicidal ideation will decrease within their population.